Study on Microstructure and Hot Deformation Behavior of High Chromium Cast Iron/Low Carbon Steel Laminate - G. Yuan; C. Yan; H. Wu; X. Xiao; S. Zhao; Z. Yu (Archives of Metallurgy and Materials)
A hot compression process was developed to study the hot deformation behavior and microstructure of a high chromium cast iron/low carbon steel laminate on a Gleeble 3800 thermal simulation test machine at a temperature of 950-1200℃. The deformation characteristics and the microstructure evolution of the specimens were investigated. Experimental results showed that the monolithic high chromium cast iron specimen cracked during hot compression, but the formability of brittle cast iron in the core of the sandwich structure was improved. Besides, the two metals showed better coordination deformation performance after hot compression treatment at 1150℃. The simultaneous deformation of high chromium cast iron and the ductile carbon steel changed the deformation mode of the cast iron and reduced the normal stress that the cast iron bore. The coarse carbides in cast iron fractured and dissolved into the matrix after hot compression. The interface between the two metals was well bonded without any interfacial cracks and voids produced, forming a corrugated shape.